Champa in the Medieval Islamic Sources - Pham Thi Thanh Huyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The establishment and spread of Islam have been associated with the continuity and development of long-distance trade. For a long time, merchants from the Islamic World dominated important trade routes in the Indian Ocean, and the Mediterranean connecting East-West trade. Hence, the information on ports and stopping points increased and contributed to the expanded knowledge of remote lands. On the way to China via the east half of the Indian Ocean, trading ships from the Islamic World anchored on several ports including Champa. So how was Champa described in the writings of the Islamic World? This article introduces central components of Islamic geographical imagination towards Champa and obstacles triggered by the worldview as well as the writing and copying process which we need to bear in mind to dig in further in detail for each toponym. As a case study, the article will analyze the description of Champa-related toponyms in Al-Mas’ūdī’’s Meadows of Gold and Mines of Gems (10th century) and the way those toponyms are mapped by Park Hyunhee- a modern historian. Received 10th February 2023; Revised 10th March 2023; Accepted 29th March 2023